Study protocol for a randomized clinical trial evaluating the safety and efficacy of autologous adipose-derived stem cell therapy for ulcers in patients with critical limb ischemia - de Oliveira Filho, Francisco José [UNESP]; da Silva Rodrigues, Lenize [UNESP]; do Amaral, Sidia Maria Baptista [UNESP]; Mellucci Filho, Pedro Luciano [UNESP]; Medolago, Natália Bronzatto [UNESP]; de Carvalho Bovolato, Ana Lívia [UNESP]; de Cássia Alvarado, Rita [UNESP]; Bertanha, Matheus [UNESP] (Public Library of Science (PLoS), 2025)
Background Peripheral artery disease (PAD) can develop into critical limb ischemia (CLI), which is characterized by resting pain at rest, ulcerations, or gangrene, with a high risk of amputation. The optimum course of treatment at this point is arterial revascularization, although this has a significant financial cost and is not always feasible or successful in reducing pain, healing ulcers, or preventing amputations. In situations where traditional alternatives for treating PAD have been exhausted, recent developments in cell therapy may offer a viable substitute. Objective The purpose of this study is to assess the safety and effectiveness of using expanded autologous adipose-derived stem cells (ASCs) in cellular therapy for the treatment of PAD patients who developed chronic artery ulcers. Methods An open randomized clinical trial will be carried out with two groups of twenty patients with CLI: In group 1, 2g of abdominal adipose tissue will be taken to produce ASCs. These cells will then be expanded in a lab (cell processing center) for 14–21 days before being applied to the lesion using bio-dressings and perilesional subcutaneous injections. Group 2 will receive conventional treatment with hydrogel-based dressing. There will be regular clinical assessments, supplementary tests, and photo documentation. The main efficacy outcome will be partial or complete healing of the wound. Safety outcomes will be monitored for infections, gangrene, amputations, and death. Participants will be monitored for 90 days. Cases of major amputation of the studied limb will not be included. The results will be evaluated by an independent external evaluator who is blind to the groups. Considering the high prevalence and socioeconomic consequences related to CLI and limb amputation, this study is expected to provide a positive social and financial impact on the Brazilian Unified Health System.